Sosialisasi Meningkatkan Penghasilan Menggunakan Media Sosial Ibu Rumah Tangga di Majelis Taklim (Lingkar Barat) Masjid Al - Muttahid - Annisa, Okta Feranica; Hidayah, Nenden Restu; Afriani, Sulisti; Anggriani, Ida (LPPM Universitas Dehasen Bengkulu, 2024)
Socialization activities at the Al-Muttahid Mosque (West Circle) Islamic boarding school aim to empower housewives with digital marketing skills that can increase family income. This socialization includes a basic understanding of digital marketing, use of major digital platforms such as social media and online marketplaces, as well as effective marketing strategies. Through a practical approach and case studies, it is hoped that participants can apply the knowledge gained to promote their products or services more widely and efficiently. The results of this activity are expected to improve housewives' digital marketing skills, expand market reach, and ultimately increase family income. This research uses participatory methods with direct observation and interviews to evaluate the effectiveness of this socialization